CONTINUING EDUCATION IN THE ERA OF ARTIFICIAL INTELLIGENCE: PRACTICE OF USING MICROSOFT COPILOT CHAT IN PROFESSIONAL TRAINING OF EDUCATORS - Osadcha , Kateryna; Osadchyi , Viacheslav (Continuing Professional Education: Theory and Practice, 2025)
The article deals with the analysis of approaches and strategies for training teachers to use artificial intelligence (AI) in their professional activities and determining teachers’ opinions on the potential of Microsoft Copilot Chat to assist in pedagogical work, in particular in performing certain professional tasks (creating speeches, developing lecture plans, generating ideas for assessment, selecting illustrations, etc.). To achieve this goal, the study used the theoretical analysis of current research and experience in improving the professional training of teachers in AI use, as well as an empirical survey method. Theoretical analysis was used to identify the approaches and strategies proposed by researchers for the professional training of teachers in the field of AI. The use of the empirical method made it possible to find out the opinions of teachers regarding the possibilities of using Microsoft Copilot Chat in their professional activities. It was found that researchers propose the following approaches to improving teachers’ qualifications in AI: hybrid-flexible, cyclical, mixed theoretical-practical, and step-by-step approaches. The following strategies for effective training of teachers in AI technologies were identified: case-oriented professional development programs; role-playing games on the integration of AI tools; scenario-based activities; seminars; discussions; practical design work and interactive classes; activities to develop critical thinking; virtual modeling; organization of groups for collaborative work; engagement through team design activities; AI-assisted learning, AI learning, and AI preparation; combination of personalized learning trajectories, intelligent learning tools, virtual/augmented reality learning environments, and educational data analysis; training and consulting on the integration of AI technologies into the educational process.